Optimization of technical productivity of a bulldozer unit in terms of traction and speed parameter - I. Р. Troyanovskaya; О. A. Grebenshchikova (Вестник СибАДИ, 2025)
Introduction. Industrial tractor units differ from agricultural tractor units by the greater weight of the working equipment, a wide range of soil conditions and the cyclicity of the technological cycle. An integral part of the operation of bulldozer units is slippage, which is not regulated by GOST. However, large amounts of slippage result in a drop in operating speed and technical performance. Therefore, the approaches developed for optimizing the productivity of tracked agricultural tractor units (where slippage is regulated at 5%) require clarification. The aim of the study is to determine the influence of specific traction-speed characteristics of a bulldozer unit on its technical productivity.Materials and methods. Technical productivity was defined as the ratio of the volume of developed soil to the time of the working cycle. The volume of developed soil was expressed through the specific traction indicators of the tractor unit. The time of the working cycle was expressed through the speed indicators of the tractor unit. As a result, the dependence of technical productivity on the specific traction-speed indicators of the industrial tractor unit was obtained.Results. The analysis of this dependence showed the presence of a clearly expressed maximum, which for the bulldozer unit is observed at 18% slippage. Optimal specific traction efforts for various soil conditions were determined. The evaluation of the speed indicators of the bulldozer unit showed the possibility of additional increase in technical productivity due to the growth of the operating speed.Conclusions. A productivity coefficient has been obtained that allows comparing the technical indicators of tractor units of different classes. It has been established that for bulldozer units with a semi-rigid suspension, operating on dense soils, the optimal specific traction efforts are 0.75...0.89. Further increase in technical productivity is possible by increasing the working speed while maintaining (or increasing) the ratio of idle speed to working speed.